Pendidikan Etika Spiritual Perspektif Al-Ḥarist Al-Muhasibi dan Relevansinya terhadap Pendidikan Modern - Moh Saifulloh Ma'sum; Nasrulloh (Al-Kindi, 2025)
This research discusses the concept of spiritual-ethical education in Risālah al-Mustarsyidīn by al-Ḥārisṯ al-Muḥāsibī and its relevance to the needs of modern education. Through a library research approach, this study analyzes al-Muḥāsibī’s thoughts on spiritual development through purification of the soul (tazkiyah al-nafs), self-reflection (muhāsabah. Al-Muḥāsibī emphasized that educational success is not only measured by academic achievement, but also by the quality of character, morals, and spirituality of learners. In his view, education is the integration of knowledge, faith, and complete human being (al-insān al-kāmil).The results of the study indicate that al-Muḥāsibī’s spiritual-ethical education has strong relevance to the modern educational world, serious challenges such as moral degradation, character crisis, and weak spiritual control due to the influence of globalization and technology. The concept of spiritual-ethical education in Risālah al-Mustarsyidīn can serve as an alternative solution to strengthen character education through a holistic and balanced approach y. The implementation of al-Muḥāsibī’s educational values is expected to produce knowledgeable, ethical individuals who contribute positively to society and civilization.